Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÐºÑ€Ð¸Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ð¾Ð² Ð½Ð° ÑƒÑ€Ð¾Ð²ÐµÐ½ÑŒ Ð³Ð¸Ð¿ÐµÑ€Ñ‚Ð¾Ð½Ð¸Ñ‡ÐµÑÐºÐ¾Ð³Ð¾ ÐºÑ€Ð¸Ð¾Ð³ÐµÐ¼Ð¾Ð»Ð¸Ð·Ð° ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° Ñ Ð¼Ð¾Ð´Ð¸Ñ„Ð¸Ñ†Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ð¼ Ñ†Ð¸Ñ‚Ð¾ÑÐºÐµÐ»ÐµÑ‚-Ð¼ÐµÐ¼Ð±Ñ€Ð°Ð½Ð½Ñ‹Ð¼ ÐºÐ¾Ð¼Ð¿Ð»ÐµÐºÑÐ¾Ð¼ - Cherkashina, Ya. O. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2012)
There was studied the development of hypertonic cryohemolysis of erythrocytes, modified with iodoacetamide (IAA) and pchlormercuribenzoate (p-CMB) in the media containing cryoprotectants (glycerol, 1,2-propane diol, polyethylene glycerol-1500). It has been shown that independently on the presence in the incubation medium of cryoprotective compounds when modifying the protein component of erythrocytes with IAA and p-CMB the sensitivity of erythrocytes to hypertonic cryohemolysis increases. This may be stipulated with the change in conformation of the proteins directly or indirectly involved into adaptation mechanisms of cells to stress effects.